2012
DOI: 10.1186/1471-2164-13-731
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of microRNAs from lactating and non-lactating bovine mammary glands and identification of miRNA related to lactation

Abstract: BackgroundMicroRNAs (miRNAs) have been implicated in the regulation of milk protein synthesis and development of the mammary gland (MG). However, the specific functions of miRNAs in these regulations are not clear. Therefore, the elucidation of miRNA expression profiles in the MG is an important step towards understanding the mechanisms of lactogenesis.ResultsTwo miRNA libraries were constructed from MG tissues taken from a lactating and a non-lactating Holstein dairy cow, respectively, and the short RNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 40 publications
8
128
0
1
Order By: Relevance
“…The profiles of miRNAs in bovine MG tissue or milk have been investigated using different approaches, such as microarray [48,49], genome sequencing [4] and RNA sequencing [50][51][52][53][54][55][56][57]. A total of 496 miRNA genes were identified following sequencing of the cattle genome of which 135 were novel [4].The expression profiles of miRNAs in MG tissues and cells facilitate discovery of novel miRNAs and also identification of candidate miRNAs for different cell types, lactation stages, periods, disease response and so on.…”
Section: Cattlementioning
confidence: 99%
See 2 more Smart Citations
“…The profiles of miRNAs in bovine MG tissue or milk have been investigated using different approaches, such as microarray [48,49], genome sequencing [4] and RNA sequencing [50][51][52][53][54][55][56][57]. A total of 496 miRNA genes were identified following sequencing of the cattle genome of which 135 were novel [4].The expression profiles of miRNAs in MG tissues and cells facilitate discovery of novel miRNAs and also identification of candidate miRNAs for different cell types, lactation stages, periods, disease response and so on.…”
Section: Cattlementioning
confidence: 99%
“…Using microarray, Izumi et al [59] identified 100 and 53 known miRNAs in colostrum and mature milk, respectively. Using Solexa sequencing method, Li et al [60] reported 884 unique miRNAs sequences in the bovine MG (283 known, 505 novel and 96 conserved miRNAs). Le Guillou et al [61] identify 167 novel miRNAs in the bovine MG, many of which were also detected in mouse MG. Analysing three milk fractions (fat, whey and cells) and mammary gland tissues, we reported 210, 200 and 249 known and 33, 31 and 36 novel miRNAs in milk fat, whey and cells, respectively, and 321 known and 176 novel miRNAs in mammary gland tissues [62].…”
Section: Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding livestock species, the choice of methods for miRNA discovery and novel miRNA annotation vary among studies and species. For example, De Vliegher et al [85] used miRbase [86] and UNAFold [87] for miRNA annotation and discovery in bovine mammary gland tissues while Peng et al [88] used miRbase [86] and RNAfold [89] for these purposes in porcine mammary glands. In our own studies, miRbase [86] and mirDeep2 [74] were used to identify miRNAs in various tissues including bovine mammary gland tissues [90], milk fat [90][91][92], milk whey and cells [90].…”
Section: Tools For Mirna Identiicationmentioning
confidence: 99%
“…MiRNA profile changes in mastitis-affected cows may be important information and, as the authors suggest, may play a crucial role in the treatment of mastitis in Holstein cattle. Bovine miRNA has also been analyzed in studies by Li et al (36). The authors described the expression profile of microRNAs from lactating and non-lactating bovine mammary glands (MG) and the identification of miRNAs related to lactation.…”
Section: Biogenesismentioning
confidence: 99%